Pengaruh Penilaian Kinerja dan Pengembangan Kompetensi terhadap Motivasi Kerja yang Dimediasi Variabel Pengembangan Karir - Faris Rizky Kurniawan; Lies Putriana; Seta A Wicaksana (Syntax Corporation Indonesia, 2025)
This study aims to analyze the impact of performance appraisal and competency development on work motivation, with career development as a mediating variable at Bank Indonesia. The research employs a quantitative approach using survey methods. The findings reveal that performance appraisal and career development have a positive and significant influence on work motivation, while competency development does not have a direct significant effect. Additionally, career development significantly mediates the influence of performance appraisal and competency development on work motivation. These findings highlight the importance of integrating performance appraisal systems, career development programs, and competency development to maximize employee potential and enhance work motivation at Bank Indonesia.